Design and Construction of a Spinner using Low Cost Materials - Santos, J. V. A.; Santos, C. P.; Macedo, M. A. (Scientia Plena, 2012)
In this paper we show how to build equipment spinner applied to the deposition of thin films by spincoating process, using inexpensive components easily found on the market and allow for easy assembly. This equipment allows us to control the speed of rotation of the sample holder, causing the substrate to rotate at a constant speed and acceleration through the centripetal effect of the thin film is deposited on the substrate surface. Details of the construction of the mechanical, electrical and a method for the calibration are presented. We found a linear frequency versus the electrical potential of the engine reaching speeds above 2000 rpm.